The importance of Research and Development expenditure for the competitiveness of manufacturing enterprises in Poland. The application of panel models - Grzelak, Maria M.; Laskowska, Iwona; Roszko-Wójtowicz, Elżbieta (Znaczenie nakładów na działalność badawczo-rozwojową dla konkurencyjności przedsiębiorstw przetwórstwa przemysłowego w Polsce. Zastosowanie modeli panelowych, 2018)
In contemporary research and economic discussions, a great deal of attention is paid to issues concerning the relationship between competitiveness and research and development (R&D) activity. The measurement and assessment of the impact of R&D activity are extremely difficult but at the same time very important, in particular for authorities determining the level of expenditure on R&D and the method of spending public funds as well as for enterprises assessing the expected profits derived from R&D. The main aim of the article is an attempt to quantify the impact of R&D expenditure on three selected characteristics defining the competitiveness of manufacturing enterprises (gross value added, sold production and labour productivity). The analysis was carried out using panel models. The study makes use of statistical data published by the Central Statistical Office for individual divisions of manufacturing (Section C of the Polish Classification of Activities – PKD) in the years 2009-2016. The conducted analyses indicate that R&D expenditure constitutes a significant determinant of the competitiveness of the analysed divisions of manufacturing
Econometrics = Ekonometria, 2018, Vol. 22, No. 3, s. 9-22
Keywords: R&D expenditures; competitiveness; manufacturing; panel models; nakłady na B+R; konkurencyjność; przetwórstwo przemysłowe; modele panelowe